Global exposure to river and coastal flooding: Long term trends and changes - Jongman, Brenden; Ward, Philip J.; Aerts, Jeroen C.J.H. (Global environmental change, 2012)
[Display omitted] ► Global assessment of economic exposure to flooding of river and coastal systems. ► Two methods for quantitative assessment, one based on population and one on land-use. ► Analysis conducted for 1970–2050, using global historical spatial data and projections. ► Economic flood exposure is simulated to increase by circa 200% between 2010 and 2050. ► Growth of human population and economic value in flood zones higher than overall growth. Flood damage modelling has traditionally been limited to the local, regional or national scale. Recent flood events, population growth and climate change concerns have increased the need for global methods with both spatial and temporal dynamics. This paper presents a first estimation of global economic exposure to both river and coastal flooding for the period 1970–2050, using two different methods for damage assessment. One method is based on population and the second is based on land-use within areas subject to 1/100 year flood events. On the basis of population density and GDP per capita, we estimate a total global exposure to river and coastal flooding of 46 trillion USD in 2010. By 2050, these numbers are projected to increase to 158 trillion USD. Using a land-use based assessment, we estimated a total flood exposure of 27 trillion USD in 2010. For 2050 we simulate a total exposure of 80 trillion USD. The largest absolute exposure changes between 1970 and 2050 are simulated in North America and Asia. In relative terms we project the largest increases in North Africa and Sub-Saharan Africa. The models also show systematically larger growth in the population living within hazard zones compared to total population growth. While the methods unveil similar overall trends in flood exposure, there are significant differences in the estimates and geographical distribution. These differences result from inherent model characteristics and the varying relationship between population density and the total urban area in the regions of analysis. We propose further research on the modelling of inundation characteristics and flood protection standards, which can complement the methodologies presented in this paper to enable the development of a global flood risk framework.